The Role of Christian Ethics Education In Character Development of Catholic University Students In Indonesia - Christina Esti Susanti; Benny Suwito (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Background: Catholic higher education seeks to integrate academic formation with moral and faith-based development, yet empirical evidence on how students' perceptions of Christian ethics education relate to their character remains limited. Aim: This study examined the relationship between Christian Ethics Education and Student Character among Catholic university students in Indonesia. Methods: A quantitative survey was conducted with 200 active students selected through purposive sampling from the population of APTIK-affiliated higher education institutions. Christian Ethics Education was measured with 29 items and Student Character with 16 values using a five-point Likert scale. Data were processed using SPSS, including descriptive statistics, validity and reliability testing, and hypothesis testing. Results: Christian Ethics Education had a mean of 4.41558 (SD = 0.73149), and Student Character had a mean of 4.29947 (SD = 0.95667). Cronbach's alpha was 0.972 and 0.962, respectively. The reported hypothesis test yielded a coefficient/loading of 0.874, t = 24.355, and p = 0.0000, indicating a strong positive statistical relationship in the surveyed sample. Conclusion: Higher reported Christian Ethics Education was associated with stronger self-reported Student Character. Because the study used survey data, the result should be interpreted as an association rather than proof of a causal effect.